Variation in polygalacturonase production among Aspergillus flavus isolates. - Cotty, P J (1990)
Pectinase production by Aspergillus flavus was determined by measuring clear zones formed around colonies stained with ruthenium red. Several isolates produced red zones instead of clear zones. Red zones were reproduced with pectinesterase and correlated with absence of specific polygalacturonases. Of 87 isolates tested, 15 produced red zones.